Effect of protein adsorption on the dissolution kinetics of silica nanoparticles - Ali, Muhammad Saad; Uttinger, Maximilian; Romeis, Stefan; Schmidt, Jochen; Peukert, Wolfgang (Colloids and Surfaces B-Biointerfaces, 2022)
Nanoparticulate systems in the presence of proteins are highly relevant for various biomedical applications such as photo-thermal therapy and targeted drug delivery. These involve a complex interplay between the charge state of nanoparticles and protein, the resulting protein conformation, adsorption equilibrium and adsorption kinetics, as well as particle dissolution. SiO2 is a common constituent of bioactive glasses used in biomedical applications. In this context, the dissolution behavior of silica particles in the presence of a model protein, bovine serum albumin (BSA), at physiologically relevant pH conditions was studied. Sedimentation analysis using an analytical ultracentrifuge showed that BSA in the supernatant solution is not affected by the presence of silica nanoparticles. However, zeta potential measurements revealed that the presence of the protein alters the particles' charge state. Adsorption and dissolution studies demonstrated that the presence of the protein significantly enhances the dissolution kinetics via interactions of positively charged amino acids in the protein with the negative silica surface and interaction of BSA with dissolved silicate species. Our study provides comprehensive insights into the complex interactions between proteins and oxide nanoparticles and establishes a reliable protocol paving the way for future investigations in more complex systems involving biological solutions as well as bioactive materials.